Bernoullian influences on Leonhard Euler's early fluid mechanics. Issue 2 (4th May 2019) - Tou, Erik R.
Abstract : Today, Leonhard Euler receives most of the credit for developing the basic theory of fluids, and modern fluid mechanics is indeed descended from his original insights. However, fluid mechanics as originally conceived by Euler is strikingly different in appearance from today's treatment of the subject. Here, we examine two of Euler's earliest works in fluid mechanics – first, an extract from a letter to Johann Bernoulli, and second, an early manuscript published many years after it was written. From these works, we see the influence that Daniel and Johann Bernoulli had on the development of Euler's ideas.